A research study of sentiment analysis and various techniques of sentiment classification. (2016) - Dubey, Gaurav; Rana, Ajay; Ranjan, Jayanthi
Sentiment analysis or opinion mining is a deterministic technique for classifying and evaluating other people's opinions. Nowadays, people build their perception and make decisions by analysing the facts and reviews of other people either manually or computationally. Since everything is online nowadays, internet has become an integrated part of human lives and is thus used for exchanging all aspects of human life viz. sentiments, emotions, affection, support, opinions, trade, business, etc. With the onset of social media there has been numerous platform such as blogs, discussion forums, reviews and social networks where an individual can post his or her reviews, feedbacks and list their likes and dislikes for a product's attributes or features or comparison of different products (same or different feature). These reviews are gathered and are analysed to evaluate the overall orientation of the collected reviews. This survey paper focuses on in-depth study of the topic and discusses all concepts and terminologies of opinion mining. This paper also discusses the methods and techniques used for gathering reviews, extracting the phrases based on the subjectivity (Esuli and Sebastiani, 2006) and thereafter calculating the semantic orientation of the collected reviews.